Pembentukan Undang-Undang Etika Lembaga Perwakilan (Sebuah Kajian Akademik) - Marzuki Marzuki (Universitas Islam Sumatera Utara, 2018)
Abstract To strengthen parliamentary institutions, in 2016 there was a study of the essence of the establishment of a law on the ethics of representative institutions to regulate the ethics of representative institutions both in internal and external relations. In this context, ethics is more synonymous with human attitudes and behavior, and with not institutions, so basically ethical issues are sufficiently regulated internally. But, the needed is the Law on the Relationship of Representative Institution Work Procedures because in practice the clash often occurs between State institutions, such as the DPR (House of Representatives) and DPD (Regional Representative Council), the Judicial Commission and the Supreme Court, which is legally constitutionally regulated in the 1945 Constitution of the Republic of Indonesia. Keywords: Establishment of Law, Ethics of the House of Representatives